Analisis Penerapan Metode Umpan Balik 360 Derajat dalam Evaluasi Kinerja Karyawan di Bagian Preventive Maintenance PT. Doulton - Abdul Aziz; Deva Siviana; Syamsul Hidayat (MASMAN Master Manajemen, 2026)
This study aims to analyze the implementation of the 360-degree feedback method in employee performance evaluation in the Preventive Maintenance department of PT. Doulton. Employee performance evaluation is a crucial element in an organization to ensure work effectiveness, competency improvement, and continuous development of human resource quality. This study uses performance assessment data from six employees with indicators in the form of assessment scores, performance categories, feedback, and corrective action plans. The results show that employee performance assessment scores range from 28.6 to 40.2, with the majority of employees falling into the “adequate” performance category. The findings also indicate that the dominant aspects of feedback are the need to improve consistency, communication, initiative, and work effectiveness. The most recommended follow-up strategy is coaching, while for employees with excellent performance, development through leadership training and promotion is recommended. Conceptually, the implementation of feedback-based performance evaluation has supported the principle of continuous development, but the implementation of the 360-degree method still requires strengthening, especially in the multi-source aspect of assessment to be more objective, comprehensive, and in accordance with the theoretical characteristics of 360-degree feedback. Thus, implementing this method can be an effective strategy for improving employee performance and career development in the Preventive Maintenance department if implemented systematically and involving various assessors.